The Purchasing Decisions of Sharia Insurance Products During Covid-19 Period; Effectiveness of Theory Planned Behavior - Syihabudin, Syihabudin; Najmudin, Najmudin (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2023)
This study aims to determine effect of attitudes on the decision to buy sharia insurance products during the covid-19 period, effect of subjective norms on the decision to buy sharia insurance products during the covid-19 period, effect of perceived control behavior on sharia insurance decisions during the covid-19 period, and effect of the theory of planned behavior which includes attitudes, perceived control behavior on the decision to buy sharia insurance products during the covid-19 period. The object of this research is Sharia Prudential Insurance in Serang-Banten Regency. Respondents who became the population of this study were Prudential Sharia Insurance customers in Serang-Banten Province. The sample taken in this study amounted to 80 respondents. The research method used is quantitative. Methods of data collection using a questionnaire. Data were analyzed using the multiple linear regression method. The results of this study show that  Attitudes have a significant positive effect on the decision to buy sharia insurance products during the covid-19 period, subjective norms have a significant positive effect on the decision to buy sharia insurance products during the covid-19 period, Perceived control behavior has a significant positive effect on the decision to buy sharia insurance products during the covid-19 period, and attitudes, subjective norms and perceived control behavior simultaneously have a significant positive effect on the decision to buy sharia insurance products during the covid-19 period